Human management and landscape changes at Palaikastro (Eastern Crete) from the Late Neolithic to the Early Minoan period - Cañellas-Boltà, Nuria; Riera-Mora, Santiago; Orengo, Hector Aleix; Livarda, Alexandra; Knappett,, Carl (Elsevier, 2018)
On the east Mediterranean island of Crete, a hierarchical society centred on large palatial complexes emerges during the Bronze Age. The economic basis for this significant social change has long been debated, particularly concerning the role of olive cultivation in the island's agricultural system. With the aim of studying vegetation changes and human management to understand the landscape history from Late Neolithic to Bronze Age, two palaeoenvironmental records have been studied at Kouremenos marsh, near the site of Palaikastro (Eastern Crete). Pollen, NPP and charcoal particles analyses evidenced seven phases of landscape change, resulting from different agricultural and pastoral practices and the use of fire probably to manage vegetation. Moreover, the Kouremenos records show the importance of the olive tree in the area. They reflect a clear trend for its increasing use and exploitation from 3600 cal yr BC (Final Neolithic) to the Early Minoan period, that is coeval with an opening of the landscape. The increase of Olea pollen was due to the expansion of the tree and its management using pruning and mechanical cleaning. The onset of olive expansion at c. 3600 cal yr BC places Crete among the first locales in the eastern Mediterranean in the management of this tree. Between c. 2780 and 2525 cal yr BC the landscape was largely occupied by olive and grasslands, coinciding with an increase in grazing practices. The high Olea pollen percentages (40-45%) suggest an intensive and large-scale exploitation of the olive tree. The results suggest that a complex and organized landscape with complementary land uses and activities was already in place since the Final Neolithic. The notable expansion of olive trees suggests the relevance of olive exploitation in the socio-economic development of Minoan towns of eastern Crete. Other crops, such as cereals and vine, and activities such as grazing have also played an important role in the configuration of the past landscape.